Metro Iloilo Development Council: In Pursuit of Managed Urban Growth - Janet S. Cuenca; Eden C. Villanueva-Ruiz (Philippine Institute for Development Studies (PIDS), 2004)
This paper aims to present the experience of MIDC in its pursuit for a highly livable region of God-loving and educated people working together for a progressive, self-reliant and sustainable community. It provides the socioeconomic development in Iloilo City, MIDCs core city and delves into urbanization issues and responses of Iloilo City in terms of resource mobilization and allocation, and delivery of basic services. It also gives a background on the creation of MIDC and highlights the experience of MIDC in working together towards the attainment of its vision.
Keywords: 330; metropolitan arrangements; Metropolitan Iloilo Development Council (MIDC); Iloilo City; interlocal government cooperation; metropolitanization